Comparative Evaluation of Pain Perception of 2% Lignocaine and 4% Articaine in Inferior Alveolar Nerve Block among Pediatric Dental Patients: An Observational Study - Dr. Kanchan Sharma; Dr. Bitra Deepti; Dr. Sumit Bhatt; Dr. Akanksha Baheti; Dr. Vaishali Ulhas Bhalerao; Dr. Sudipta Kar (The Bioscan, 2025)
Aim: This study aimed to compare and assess the pain perception of 2% lignocaine with 1:80,000 epinephrine against 4% articaine with 1:100,000 epinephrine in children. Material and Method: A split-mouth randomized controlled trial was carried out involving 20 children aged 4 to 8 year who required inferior alveolar nerve block (IANB) anesthesia for dental work in the lower jaw. Pain perception was evaluated using a visual analog scale (VAS) where patients rated their subjective pain, alongside the FLACC scale, which assessed objective pain through the operator's observations of the child's face, legs, activity, crying, and ability to be consoled.